Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-00394-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Association Between Demographics, SLC30A8 Genotype, and Human Islet Content of Zinc, Cadmium, Copper, Iron, Manganese and Nickel

Abstract: A widely prevalent single nucleotide polymorphism, rs13266634 in the SLC30A8 gene encoding the zinc transporter ZnT8, is associated with an increased risk for T2DM. ZnT8 is mostly expressed in pancreatic insulin-producing islets of Langerhans. The effect of this variant on the divalent metal profile in human islets is unknown. Additionally, essential and non-essential divalent metal content of human islets under normal environmental exposure conditions has not been described. We therefore examined the correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 71 publications
4
33
0
Order By: Relevance
“…This report also noted that the T2D-risk R325 ZnT8 variant consistently showed a small increase in zinc transport activity compared to the T2D-protective W325 variant, which was revealed only with specific lipid compositions of the liposomes. In accordance with higher transport activity, it was noted that human islets with the R325 ZnT8 variant had a higher zinc content [41]. Another report on ZnT8 transport in Xenopus laevis oocytes did not detect a difference in transport kinetics between the ZnT8 R/W325 variants, supporting the conclusion that the liposome lipid composition may be crucial for revealing differences between the two variants [42].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This report also noted that the T2D-risk R325 ZnT8 variant consistently showed a small increase in zinc transport activity compared to the T2D-protective W325 variant, which was revealed only with specific lipid compositions of the liposomes. In accordance with higher transport activity, it was noted that human islets with the R325 ZnT8 variant had a higher zinc content [41]. Another report on ZnT8 transport in Xenopus laevis oocytes did not detect a difference in transport kinetics between the ZnT8 R/W325 variants, supporting the conclusion that the liposome lipid composition may be crucial for revealing differences between the two variants [42].…”
mentioning
confidence: 77%
“…How or even if these effects in the CTDs lead to the altered transport function of the full‐length proteins reported elsewhere , and ultimately to the relatively large increased risk of developing T2D for carriers of the R325 variant, will require further investigation. That the T2D‐risk ZnT8 R325 variant is the more active form of the transporter suggests that people with the R325 variant may have an increased zinc content in their insulin granules as indicated by the data on human islets . This increased granular zinc uptake may deplete cytosolic zinc and affect β‐cell function.…”
Section: Discussionmentioning
confidence: 98%
“…LoF p.Arg138* (assuming no or minimal escape from NMD) is therefore likely to exert the same effects on intracellular zinc concentrations and may thus impact insulin secretion through intracellular mechanisms, including potential differences in Zn 2+ secretion. Also, a recent study showed that the p.Arg325Arg variant was associated with higher islet zinc concentrations 27 . In the present study over-expression of the LoF mutation p.Arg138* in INS-1 cells did not result in changes in cytosolic zinc concentrations leaving a reduction of zinc in insulin granules as a plausible explanation which still needs to be experimentally confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…With the approximate Cu II /C‐peptide affinity determined from competition with phen, Cu II would be able to displace Zn II from C‐peptide if the concentrations of both metals were within one to two orders of magnitude. In addition to the millimolar concentrations of Zn II in the secretory vesicles of pancreatic beta‐cells, there are high micromolar concentrations of Cu II . Under these conditions and in conjunction with the approximate nanomolar affinity, Cu II /C‐peptide may exist in the vesicles along with Zn II /C‐peptide.…”
Section: Figurementioning
confidence: 99%